Effect of yttrium oxide modification of Al-Si alloy on microhardness and microstructure of surface layers - S. V. Konovalov; D. V. Zagulyaev; Y. F. Ivanov; V. E. Gromov (Metalurgija, 2018)
Microhardness, structure and phase state of silumin modified by coating with yttrium oxide when electroexplosive alloying were analyzed. Appropriate processing modes were estimated according to the results of research. The study on the structure and phase composition was carried out for the processing mode, which increases microhardness of the surface layer more than twice. A complex of research procedures was used to analyze the structure and phase composition. As revealed in the study, the coatings with a thickness of 50 – 80 μm are highly rough and porous, they have a sub-micro- and nano-scaled multiph ase structure with particles of silicon, Y2O3, YSi2 and Y2Si2O7 as strengthening phases, and alloying elements (silicon, yttrium, and oxygen) don’t tend to spread homogenously in them.